IMPLEMENTATION OF ONLINE DISPUTE RESOLUTION AND MARKETPLACE LIABILITY BASED ON THE PRINCIPLE OF INTERMEDIARY LIABILITY - Maslihati Nur Hidayati; Suartini Suartini (Asosiasi Dosen Muda Indonesia, 2024)
The rapid growth of online transactions aligns with the increasing potential for disputes between consumers and businesses. The problem is the need for national regulations governing ODR, although some marketplaces have implemented internal dispute resolution systems. This research uses John Rawls' theory of distributive justice to analyze marketplace liability in online dispute resolution, focusing on the principle of intermediary liability. The research method involves a literature review and case analysis on several platforms such as Tokopedia, Shopee, AliExpress, and eBay. The results show that although some marketplaces have developed efficient ODR systems, there are still challenges related to transparency, security, and fairness. Marketplaces are expected to create a more comprehensive and equitable system, considering equal access for consumers.